RANCANG BANGUN APLIKASI MARKETPLACE PETANI HIDROPONIK BERBASIS ANDROID DI KABUPATEN BANYUWANGI - Moh. Fachrul Arifin; Teguh Sutanto; Tri Sagirani (Jurnal Sistem Informasi Universitas Dinamika, 2022)
In Banyuwangi district, The understanding about hydroponics still relatively new. Business process that hydroponics banyuwangi farmer do for sales still using social media like Facebook or Whatsapp. By those social media, the income or sales they get are mostly only from inside the communities. From the results of interviews with several hydroponic farmers in Banyuwangi district, it is known that they need a solution to sell and expand the marketing of their hydroponic plants. This research will design and build marketplace application using the Waterfall model. The purpose of this research is to produce marketplace android application for hydroponics farmers in Banyuwangi district. Using this application to resolve problem about sales that we appointed at the beginning. By using Waterfall model at development and black box testing method, the result are 18 test cases with 100% success rate covering functions that have been applied to the frontend.